(untitled) (International Journal of Engineering and Computer Science, 2014)
Web Service has been playing a significant role in application development and integration. SOA enables the development of flexible large scale-applications in open environments by combining the web services. There exist many web services which has similar functional characteristics. It provides service to consumer with facilities for selecting required web services according to their functional and QoS characteristics. Important issues are a how to conveniently, accurately and efficiently retrieve the web services from large-scale repositories. The goal of the multi agent is to support web services discovery with QoS registration, verification, certification, and confirmation. In this paper, propose a novel approach for designing and developing a multi agent-based architecture and its QoS-based matching, ranking, feedback and selection algorithm for evaluating web services.